ORIGINAL PAPERTreatment of bifurcation lesions with a bifurcation-dedicated stent Multilink Frontier™. Long-term follow-up of 50 patients - Lesiak, Maciej; Rzeźniczak, Janusz; Hiczkiewicz, Jarosław; Grajek, Stefan; Pyda, Małgorzata; Skorupski, Włodzimierz; Mitkowski, Przemysław; Grygier, Marek; Prech, Marek; Baszko, Artur; Cieśliński, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2005)
Background: Percutaneous interventions of coronary bifurcations have always been a difficult challenge, with a lower success and higher complication rate than most other lesion types. Methods: Fifty patients with symptomatic stable or unstable angina and with bifurcation lesions were treated with Multilink Frontier™ bifurcation-dedicated stent. In-hospital, thirty-day and nine-month follow-up data were obtained. Repeat coronary angiography was performed only in the case of recurrence of symptomatic ischaemia. Results: The device was successfully implanted in 46 patients. During 30-day follow-up there were no cases of death, stent thrombosis or Q-wave myocardial infarction (MI). In-hospital non-Q-wave MI was diagnosed in two patients. During long-term follow-up no patient died, there was one case of Q-wave MI, and five patients (10%) underwent repeat target-lesion revascularization because of restenosis. Conclusions: Multilink FrontierTM, a stent specifically designed for treating bifurcation lesions can be used with a high procedural success rate, and a satisfactory clinical long-term outcome.